Twelve Tests for Tautology, Applied to the Routine Activity Approach - Felson, Marcus (Victims & offenders, 2025)
Two papers published in Victims and Offenders vigorously argue that the routine activity approach is tautological and therefore untestable. The current paper examines closely the original text of Cohen and Felson the 1979 paper to determine whether it is tautological or not. We apply twelve heuristic tests for tautology: (1) a verbal test, (2) a timing test, (3) an exceptions test, (4) an obstinacy test, (5) an expansion test, (6) a separability test, (7) a volatility test, (8) an experiment test, (9) an instrument test, (10) a macrosocial test, (11) a policy test, and (12) an ecosystem test. The routine activity approach (as originally presented) passes all twelve tests and is not tautological.